Using positive psychology to enhance student achievement : a schools-based programme for character education - Rae, Tina; MacConville, Ruth (London : Routledge, 2015)
'Positive psychology, properly understood and applied, offers a tremendous opportunity for improving student and teacher experiences and the overall success of any school. The connection between education and happiness is recognised to be mutually reinforcing; education helps students to be happy and happy students gain more from education. Research has confirmed what educators have long known - that happy students typically achieve more in the classroom and exam room than unhappy students and are more energetic, persistent, creative and better able to get on with others. Positive Psychology and the happy habit is unique in translating a complex literature written by academic psychologists into a highly practical resource. The activities have been designed to provide a creative and engaging way of enabling students to discover their strengths both in terms of their cognitive abilities and'virtues' i.e. character strengths.Throughout the programme students are introduced to the key insights of positive psychology:- the importance of being connected to others, Character training and metacognitive strategies Positive rather than reactive thinking and habits Developing the skills essential for building optimism and resilience, Recognising and combating negative thoughts Understanding that there are certain ways of thinking that they can make their lives better. Easy to deliver sessions with comprehensive facilitator instructions and activities resources are provided within the resource. All lessons are interactive and based on group discussions and role play to ensure students learn more about themselves and others. Students are encouraged to practise skills and ideas that are discussed during the sessions in their everyday life with home practice in the form of'take away' activities being a core element of the programme.This unique resource will be of real relevance and benefit to both staff and students at upper primary and lower secondary level and will give students within a school environment the tools they need to achieve their full potential'--
Includes bibliographical references and index.
Keywords: Academic achievement -- Psychological aspects; Educational psychology; Positive psychology; Moral education; Character -- Study and teaching